Coal aggregate composite gelling support material as well as preparation method and application thereof

By preparing coal aggregate composite cementitious support materials and utilizing solid wastes such as steel slag, blast furnace slag, and desulfurization gypsum, the problems of low bearing capacity and environmental pollution in underground coal mine working faces with open roadways were solved, achieving efficient and low-cost support effects.

CN119306458AInactive Publication Date: 2025-01-14HENAN POLYTECHNIC UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411420276.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-08-12
Filing Date
2024-10-12
Publication Date
2025-01-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing methods for using underground working faces in coal mines to pass through empty roadways have problems such as low load-bearing capacity, complicated construction, high cost, impact on production efficiency, and environmental pollution. In particular, high-water-content material support methods can reduce coal quality and hinder work progress.

Method used

A coal aggregate composite cementitious support material is adopted, which is composed of raw coal, steel slag powder, slag powder, cement clinker and desulfurized gypsum powder, etc. It is formed into a cementitious material through a simple preparation process and used for underground support in coal mines, effectively utilizing solid waste.

Benefits of technology

It improves the load-bearing capacity of support materials, reduces costs, reduces environmental pollution, improves resource utilization, and solves the problem of solid waste accumulation, thus having significant economic and social benefits.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005080567180000141
    Figure BDA0005080567180000141
Patent Text Reader

Abstract

The invention provides a coal aggregate composite gel support material as well as a preparation method and application thereof, and belongs to the technical field of preparation of composite gel support materials. The coal aggregate composite gelling support material comprises the following raw materials in parts by weight: 100-120 parts of raw coal, 40-60 parts of a gelling material, 0.6-0.9 part of an additive and 20-30 parts of water, the cementing material is composed of steel slag powder, slag powder, cement clinker and desulfurized gypsum powder, and the mass percentage of the steel slag powder to the slag powder to the cement clinker to the desulfurized gypsum powder is 6%-12%: 55%-75%: 5%-20%: 3%-12%. The problems that an existing gob roadway supporting material is low in bearing capacity, reduces coal quality and recovery efficiency and the like are solved, a large amount of solid waste such as the steel slag, the mineral slag and the desulfurized gypsum is effectively utilized, the comprehensive utilization value of the solid waste is increased, environmental hazards caused by solid waste accumulation are reduced, and the gob roadway supporting material is suitable for large-scale popularization and application. The problem of resource utilization of solid wastes is solved, and the method has important social benefits and environmental protection benefits.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of composite gel support material preparation, and in particular to a coal aggregate composite gelled support material and a preparation method and application thereof. Background Art

[0002] In order to facilitate ventilation, pedestrian and material transportation, etc., in underground coal mines, a measure tunnel, i.e., an empty tunnel, is excavated along the working face of the coal mine. When the coal mine working face passes through an empty tunnel, the superposition of the forward support pressure of the working face and the lateral support pressure of the tunnel is very likely to cause stress concentration, resulting in abnormal mine pressure and seriously affecting production safety.

[0003] At present, the commonly used methods for working faces to pass through empty tunnels mainly include using dense pillars or wood piles to support the roof of empty tunnels, using anchor rods and cables to reinforce the roof of empty tunnels, and bypassing empty tunnels to re-open and cut holes and arrange working faces. Among them, the bearing capacity of dense pillars and wood piles is relatively low. Under the influence of mining and the action of advanced support pressure, they are very easy to be damaged. The construction is cumbersome and requires a lot of labor costs. The use of anchor rods and cable support will result in a long initial construction time. When the working face is close to the empty tunnel, the surrounding rock of the empty tunnel is already in a plastic state and is not suitable for empty tunnel surrounding rock control. Re-opening and cutting holes to arrange working faces will lead to excessively high economic costs and delay production, which will have a serious impact on the economic income and other aspects of coal enterprises.

[0004] In recent years, the support method of high-water-density material pumping filling pillars has been widely used in empty tunnels at working faces in various mines. However, after mining, the filling material is mixed with coal, which reduces the quality of the coal and causes certain economic losses. Moreover, although the high-water-density material support is cuttable, it will hinder the progress of subsequent work and reduce work efficiency during the actual advancement process. Summary of the invention

[0005] The technical problem to be solved by the present invention is that in view of the deficiencies of the above-mentioned prior art, the purpose of the present invention is to propose a coal aggregate composite cementitious support material and a preparation method and application thereof. The coal aggregate composite cementitious support material has a simple component composition, abundant raw materials for preparation, a simple process and a low price. At the same time, it effectively utilizes a large amount of solid waste such as steel slag, slag, desulfurization gypsum, etc., reduces the environmental hazards caused by the accumulation of solid waste, improves the comprehensive utilization value of solid waste, and solves the problem of resource utilization of solid waste.

[0006] To achieve the purpose of the present invention, the following technical scheme is adopted:

[0007] A coal aggregate composite cementitious supporting material comprises the following raw materials in parts by weight: 100-120 parts of raw coal, 40-60 parts of cementitious material, 0.6-0.9 parts of admixture, and 20-30 parts of water.

[0008] Preferably, the particle size of the raw coal is ≤20 mm, wherein the mass percentages of the raw coal with particle sizes below 5 mm, 5-10 mm and 10-20 mm are 45%-55%: 25%-35%: 15%-20%.

[0009] Preferably, the cementitious material is composed of steel slag powder, slag powder, cement clinker and desulfurized gypsum powder, and the mass percentages of the steel slag powder, slag powder, cement clinker and desulfurized gypsum powder are 6%-12%: 55%-75%: 5%-20%: 3%-12%.

[0010] Preferably, the steel slag powder comprises, by mass percentage, 35%-40% calcium oxide, 14%-20% silicon dioxide, 20%-25% iron oxide, 1%-7% aluminum oxide and 8%-14% magnesium oxide.

[0011] Preferably, the slag powder comprises, by mass percentage, 35%-40% calcium oxide, 30%-34% silicon dioxide, 1%-5% iron oxide, 13%-17% aluminum oxide and 7%-13% magnesium oxide.

[0012] Preferably, the cement clinker comprises, by mass percentage, 60%-70% calcium oxide, 20%-24% silicon dioxide, 4%-8% aluminum oxide, 2%-5% iron oxide, and 1%-4% magnesium oxide.

[0013] Preferably, the mass content of calcium sulfate dihydrate in the desulfurized gypsum is 93%-99%.

[0014] Preferably, the admixture is an early strength water reducing agent, and the mass content of β-naphthalenesulfonate formaldehyde condensate in the early strength water reducing agent is 98%-99%.

[0015] As a preferred technical solution, the mass percentage of the raw coal particle size of less than 5mm, 5-10mm and 10-20mm is 50%-55%: 25%-30%: 15%-20%. Controlling the particle size of the raw coal within the above-mentioned specific gradation and proportion can further ensure the workability of the support material.

[0016] Further preferably, the dosage of the early strength water reducing agent accounts for 1.2%-1.5% of the mass of the cementitious material.

[0017] Still more preferably, the amount of water added accounts for 40%-60% of the mass of the cementitious material.

[0018] Another technical solution of the present invention is:

[0019] A method for preparing a coal aggregate composite gelling support material comprises the following steps:

[0020] S1, crushing, screening and grading the raw coal for standby use;

[0021] S2, drying, powdering and sieving the steel slag and slag in an oven respectively, crushing and sieving the cement clinker, crushing and sieving the desulfurized gypsum, weighing the steel slag powder, slag powder, cement clinker and desulfurized gypsum powder according to the mixing ratio and uniformly stirring to obtain a cementitious material;

[0022] S3, weighing the raw coal obtained in step S1, the cementitious material obtained in step S2, the admixture and water according to the mixing ratio, and uniformly stirring them to obtain the coal aggregate composite cementitious support material;

[0023] S4. Inject the coal aggregate composite gelling support material obtained in step S3 into the mold, and then place it on a vibration table to vibrate to remove bubbles. After that, demould the sample and place it in a constant temperature and humidity standard curing box for curing.

[0024] Preferably, in step S1, the raw coal is passed through 20 mm, 10 mm, and 5 mm sieves respectively, and then the particle sizes are classified into less than 5 mm, 5-10 mm, and 10-20 mm for later use.

[0025] Preferably, the steel slag and ore slag in step S2 are dried in an oven at 105-115° C. for 3-6 hours, ground in a φ500mm*500mm mill, and then sieved to 200 mesh for later use.

[0026] Preferably, in step S2, the cement clinker is sieved through a 3 mm sieve for later use.

[0027] Further preferably, the desulfurized gypsum in step S2 is sieved through a 3 mm sieve for later use.

[0028] Still further preferably, in step S4, the support material is injected into a 100mm×100mm×100mm cubic mold, and then placed on a vibration table for 3-5 minutes. The sample is demolded after 5-6 hours, and placed in a curing box with a temperature of 20℃±2℃ and a relative humidity of ≥95% for 3 to 28 days of curing, and the unconfined compressive strength of the support material test blocks after 3 days and 28 days of curing are tested respectively.

[0029] As another technical solution of the present invention, the coal aggregate composite cementitious supporting material is used in supporting empty tunnels at the working face of a mine.

[0030] Compared with the prior art, the present invention has the following technical effects:

[0031] 1. The coal aggregate composite cementitious support material has a simple component structure, abundant raw materials for preparation, simple process and low price. Its application as an empty tunnel support material brings huge economic benefits to coal mining enterprises.

[0032] 2. It not only breaks through the problems of low bearing capacity of existing empty tunnel support materials, reduced coal quality and recovery efficiency, but also effectively utilizes a large amount of solid waste such as steel slag, slag, desulfurization gypsum, etc., improves the comprehensive utilization value of solid waste, reduces the environmental hazards caused by the accumulation of solid waste, and solves the problem of resource utilization of solid waste, which has important social and environmental benefits. DETAILED DESCRIPTION

[0033] The following are specific embodiments of the present invention, which further describe the technical solutions of the present invention, but the present invention is not limited to these embodiments; in the following description, specific details such as specific configurations are provided only to help fully understand the embodiments of the present invention. Therefore, it should be clear to those skilled in the art that various changes and modifications can be made to the embodiments described herein without departing from the scope and spirit of the present invention.

[0034] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features of the embodiments may be combined with each other.

[0035] Example 1

[0036] A coal aggregate composite cementitious supporting material comprises the following components in parts by weight: 100 parts of raw coal, 40 parts of cementitious material, 0.6 parts of admixture and 20 parts of water.

[0037] The particle size of the raw coal is ≤20 mm, wherein the mass percentages of the raw coal with particle sizes below 5 mm, 5-10 mm and 10-20 mm are 45%:35%:20%.

[0038] The steel slag and ore slag are dried in an oven at 110°C for 5 hours, ground in a φ500mm*500mm mill and then sieved through 200 meshes; the steel slag powder includes 35% calcium oxide, 20% silicon dioxide, 25% iron oxide, 6% aluminum oxide and 14% magnesium oxide by mass percentage; the ore slag powder includes 35% calcium oxide, 34% silicon dioxide, 2% iron oxide, 16% aluminum oxide and 13% magnesium oxide by mass percentage. The cement clinker and desulfurized gypsum are sieved through a 3mm sieve respectively; the cement clinker includes 60% calcium oxide, 24% silicon dioxide, 8% aluminum oxide, 5% iron oxide and 3% magnesium oxide by mass percentage; the mass content of calcium sulfate dihydrate in the desulfurized gypsum is 93%. The steel slag powder, ore slag powder, cement clinker and desulfurized gypsum are mixed evenly in the mass percentages of 10%:75%:5%:10% to obtain a cementitious material.

[0039] The admixture is an early strength water reducing agent, and the mass content of β-naphthalenesulfonate formaldehyde condensate in the early strength water reducing agent is 98%.

[0040] The above raw coal, prepared cementitious material, admixture and water are mixed evenly according to the above weight portions to obtain coal aggregate that meets the cementitious support material, and then injected into a 100mm×100mm×100mm cubic mold, and then placed on a vibration table for vibration for 5 minutes. The sample is demoulded after 6 hours, and placed in a curing box at a temperature of 20°C and a relative humidity of 95% for curing for 3 to 28 days, and the unconfined compressive strength of the support material test blocks after curing for 3 days and 28 days are tested respectively.

[0041] Embodiment 2:

[0042] A coal aggregate composite cementitious supporting material comprises the following components in parts by weight: 100 parts of raw coal, 60 parts of cementitious material, 0.9 parts of admixture and 20 parts of water.

[0043] The particle size of the raw coal is ≤20 mm, wherein the mass percentages of the raw coal with particle sizes below 5 mm, 5-10 mm and 10-20 mm are 55%:25%:20%.

[0044] The steel slag and slag are dried in an oven at 110℃ for 5h, ground in a φ500mm*500mm mill and then sieved through 200 meshes; the steel slag powder includes 40% calcium oxide, 18% silicon dioxide, 23% iron oxide, 7% aluminum oxide and 12% magnesium oxide by mass percentage; the slag powder includes 40% calcium oxide, 32% silicon dioxide, 4% iron oxide, 14% aluminum oxide and 10% magnesium oxide by mass percentage. The cement clinker and desulfurized gypsum are sieved through a 3mm sieve respectively; the cement clinker includes 70% calcium oxide, 22% silicon dioxide, 4% aluminum oxide, 2% iron oxide and 2% magnesium oxide by mass percentage; the mass content of calcium sulfate dihydrate in the desulfurized gypsum is 99%. The steel slag powder, slag powder, cement clinker and desulfurized gypsum are mixed evenly in mass percentages of 10%:65%:20%:5% to obtain a cementitious material.

[0045] The admixture is an early strength water reducing agent, and the mass content of β-naphthalenesulfonate formaldehyde condensate in the early strength water reducing agent is 99%.

[0046] The above raw coal, prepared cementitious material, admixture and water are mixed evenly according to the above weight portions to obtain coal aggregate that meets the cementitious support material, and then injected into a 100mm×100mm×100mm cubic mold, and then placed on a vibration table for vibration for 5 minutes. The sample is demoulded after 6 hours, and placed in a curing box at a temperature of 20°C and a relative humidity of 95% for curing for 3 to 28 days, and the unconfined compressive strength of the support material test blocks after curing for 3 days and 28 days are tested respectively.

[0047] Embodiment 3:

[0048] A coal aggregate composite gelling support material comprises the following components in parts by weight: 120 parts of raw coal, 40 parts of gelling material, 0.6 parts of admixture and 20 parts of water.

[0049] The particle size of the raw coal is ≤20 mm, wherein the mass percentages of the raw coal with particle sizes below 5 mm, 5-10 mm and 10-20 mm are 50%:30%:20%.

[0050] The steel slag and ore slag are dried in an oven at 110℃ for 5h, ground in a φ500mm*500mm mill and then sieved through 200 meshes; the steel slag powder includes 37% calcium oxide, 19% silicon dioxide, 23% iron oxide, 7% aluminum oxide and 14% magnesium oxide by mass percentage; the ore slag powder includes 37% calcium oxide, 32% silicon dioxide, 3% iron oxide, 16% aluminum oxide and 11% magnesium oxide by mass percentage. The cement clinker and desulfurized gypsum are sieved through a 3mm sieve respectively; the cement clinker includes 65% calcium oxide, 22% silicon dioxide, 6% aluminum oxide, 4% iron oxide and 3% magnesium oxide by mass percentage; the mass content of calcium sulfate dihydrate in the desulfurized gypsum is 99%. The steel slag powder, ore slag powder, cement clinker and desulfurized gypsum are mixed evenly in mass percentages of 11%:74%:10%:5% to obtain a cementitious material.

[0051] The admixture is an early strength water reducing agent, and the mass content of β-naphthalenesulfonate formaldehyde condensate in the early strength water reducing agent is 99%.

[0052] The above raw coal, prepared cementitious material, admixture and water are mixed evenly according to the above weight portions to obtain coal aggregate that meets the cementitious support material, and then injected into a 100mm×100mm×100mm cubic mold, and then placed on a vibration table for vibration for 5 minutes. The sample is demoulded after 6 hours, and placed in a curing box at a temperature of 20°C and a relative humidity of 95% for curing for 3 to 28 days, and the unconfined compressive strength of the support material test blocks after curing for 3 days and 28 days are tested respectively.

[0053] Embodiment 4:

[0054] A coal aggregate composite gelling support material comprises the following components in parts by weight: 120 parts of raw coal, 40 parts of gelling material, 0.6 parts of admixture and 20 parts of water.

[0055] The particle size of the raw coal is ≤20 mm, wherein the mass percentages of the raw coal with particle sizes below 5 mm, 5-10 mm and 10-20 mm are 55%:30%:15%.

[0056] The steel slag and ore slag are dried in an oven at 110℃ for 5h, ground in a φ500mm*500mm mill and then sieved through 200 meshes; the steel slag powder includes 38% calcium oxide, 19% silicon dioxide, 24% iron oxide, 6% aluminum oxide and 13% magnesium oxide by mass percentage; the ore slag powder includes 37% calcium oxide, 34% silicon dioxide, 2% iron oxide, 16% aluminum oxide and 11% magnesium oxide by mass percentage. The cement clinker and desulfurized gypsum are sieved through a 3mm sieve respectively; the cement clinker includes 64% calcium oxide, 22% silicon dioxide, 6% aluminum oxide, 5% iron oxide and 3% magnesium oxide by mass percentage; the mass content of calcium sulfate dihydrate in the desulfurized gypsum is 99%. The steel slag powder, ore slag powder, cement clinker and desulfurized gypsum are mixed evenly in mass percentages of 12%:68%:14%:6% to obtain a cementitious material.

[0057] The admixture is an early strength water reducing agent, and the mass content of β-naphthalenesulfonate formaldehyde condensate in the early strength water reducing agent is 99%.

[0058] The above raw coal, prepared cementitious material, admixture and water are mixed evenly according to the above weight portions to obtain coal aggregate that meets the cementitious support material, and then injected into a 100mm×100mm×100mm cubic mold, and then placed on a vibration table for vibration for 5 minutes. The sample is demoulded after 6 hours, and placed in a curing box at a temperature of 20°C and a relative humidity of 95% for curing for 3 to 28 days, and the unconfined compressive strength of the support material test blocks after curing for 3 days and 28 days are tested respectively.

[0059] Embodiment 5:

[0060] A coal aggregate composite gelling support material comprises the following components in parts by weight: 120 parts of raw coal, 40 parts of gelling material, 0.6 parts of admixture and 20 parts of water.

[0061] The particle size of the raw coal is ≤20 mm, wherein the mass percentages of the raw coal with particle sizes below 5 mm, 5-10 mm and 10-20 mm are 45%:35%:20%.

[0062] The steel slag and slag are dried in an oven at 110℃ for 5h, ground in a φ500mm*500mm mill and then sieved through 200 meshes; the steel slag powder includes 38% calcium oxide, 19% silicon dioxide, 24% iron oxide, 6% aluminum oxide and 13% magnesium oxide by mass percentage; the slag powder includes 37% calcium oxide, 34% silicon dioxide, 2% iron oxide, 16% aluminum oxide and 11% magnesium oxide by mass percentage. The cement clinker and desulfurized gypsum are sieved through a 3mm sieve respectively; the cement clinker includes 64% calcium oxide, 22% silicon dioxide, 6% aluminum oxide, 5% iron oxide and 3% magnesium oxide by mass percentage; the mass content of calcium sulfate dihydrate in the desulfurized gypsum is 99%. The steel slag powder, slag powder, cement clinker and desulfurized gypsum are mixed evenly in the mass percentages of 9%:70%:17%:4% to obtain a cementitious material.

[0063] The admixture is an early strength water reducing agent, and the mass content of β-naphthalenesulfonate formaldehyde condensate in the early strength water reducing agent is 99%.

[0064] The above raw coal, prepared cementitious material, admixture and water are mixed evenly according to the above weight portions to obtain coal aggregate that meets the cementitious support material, and then injected into a 100mm×100mm×100mm cubic mold, and then placed on a vibration table for vibration for 5 minutes. The sample is demoulded after 6 hours, and placed in a curing box at a temperature of 20°C and a relative humidity of 95% for curing for 3 to 28 days, and the unconfined compressive strength of the support material test blocks after curing for 3 days and 28 days are tested respectively.

[0065] Embodiment 6:

[0066] A coal aggregate composite gelling support material comprises the following components in parts by weight: 120 parts of raw coal, 40 parts of gelling material, 0.6 parts of admixture and 20 parts of water.

[0067] The particle size of the raw coal is ≤20 mm, wherein the mass percentages of the raw coal with particle sizes below 5 mm, 5-10 mm and 10-20 mm are 50%:35%:15%.

[0068] The steel slag and slag are dried in an oven at 110℃ for 5h, ground in a φ500mm*500mm mill and then sieved through 200 meshes; the steel slag powder includes 38% calcium oxide, 19% silicon dioxide, 24% iron oxide, 6% aluminum oxide and 13% magnesium oxide by mass percentage; the slag powder includes 37% calcium oxide, 34% silicon dioxide, 2% iron oxide, 16% aluminum oxide and 11% magnesium oxide by mass percentage. The cement clinker and desulfurized gypsum are sieved through a 3mm sieve respectively; the cement clinker includes 64% calcium oxide, 22% silicon dioxide, 6% aluminum oxide, 5% iron oxide and 3% magnesium oxide by mass percentage; the mass content of calcium sulfate dihydrate in the desulfurized gypsum is 99%. The steel slag powder, slag powder, cement clinker and desulfurized gypsum are mixed evenly in a mass percentage of 8%:67%:20%:5% to obtain a cementitious material.

[0069] The admixture is an early strength water reducing agent, and the mass content of β-naphthalenesulfonate formaldehyde condensate in the early strength water reducing agent is 99%.

[0070] The above raw coal, prepared cementitious material, admixture and water are mixed evenly according to the above weight portions to obtain coal aggregate that meets the cementitious support material, and then injected into a 100mm×100mm×100mm cubic mold, and then placed on a vibration table for vibration for 5 minutes. The sample is demoulded after 6 hours, and placed in a curing box at a temperature of 20°C and a relative humidity of 95% for curing for 3 to 28 days, and the unconfined compressive strength of the support material test blocks after curing for 3 days and 28 days are tested respectively.

[0071] Embodiment 7:

[0072] A coal aggregate composite cementitious supporting material comprises the following components in parts by weight: 120 parts of raw coal, 60 parts of cementitious material, 0.9 parts of admixture and 30 parts of water.

[0073] The particle size of the raw coal is ≤20 mm, wherein the mass percentages of the raw coal with particle sizes below 5 mm, 5-10 mm and 10-20 mm are 55%:25%:20%.

[0074] The steel slag and slag are dried in an oven at 110℃ for 5h, ground in a φ500mm*500mm mill and then sieved through 200 meshes; the steel slag powder includes 38% calcium oxide, 19% silicon dioxide, 24% iron oxide, 6% aluminum oxide and 13% magnesium oxide by mass percentage; the slag powder includes 37% calcium oxide, 34% silicon dioxide, 2% iron oxide, 16% aluminum oxide and 11% magnesium oxide by mass percentage. The cement clinker and desulfurized gypsum are sieved through a 3mm sieve respectively; the cement clinker includes 64% calcium oxide, 22% silicon dioxide, 6% aluminum oxide, 5% iron oxide and 3% magnesium oxide by mass percentage; the mass content of calcium sulfate dihydrate in the desulfurized gypsum is 99%. The steel slag powder, slag powder, cement clinker and desulfurized gypsum are mixed evenly in mass percentages of 10%:70%:15%:5% to obtain a cementitious material.

[0075] The admixture is an early strength water reducing agent, and the mass content of β-naphthalenesulfonate formaldehyde condensate in the early strength water reducing agent is 99%.

[0076] The above raw coal, prepared cementitious material, admixture and water are mixed evenly according to the above weight portions to obtain coal aggregate that meets the cementitious support material, and then injected into a 100mm×100mm×100mm cubic mold, and then placed on a vibration table for vibration for 5 minutes. The sample is demoulded after 6 hours, and placed in a curing box at a temperature of 20°C and a relative humidity of 95% for curing for 3 to 28 days, and the unconfined compressive strength of the support material test blocks after curing for 3 days and 28 days are tested respectively.

[0077] Embodiment 8:

[0078] A coal aggregate composite cementitious supporting material comprises the following components in parts by weight: 100 parts of raw coal, 40 parts of cementitious material, 0.6 parts of admixture and 30 parts of water.

[0079] The particle size of the raw coal is ≤20 mm, wherein the mass percentages of the raw coal with particle sizes below 5 mm, 5-10 mm and 10-20 mm are 55%:25%:20%.

[0080] The steel slag and slag are dried in an oven at 110℃ for 5h, ground in a φ500mm*500mm mill and then sieved through 200 meshes; the steel slag powder includes 38% calcium oxide, 19% silicon dioxide, 24% iron oxide, 6% aluminum oxide and 13% magnesium oxide by mass percentage; the slag powder includes 37% calcium oxide, 34% silicon dioxide, 2% iron oxide, 16% aluminum oxide and 11% magnesium oxide by mass percentage. The cement clinker and desulfurized gypsum are sieved through a 3mm sieve respectively; the cement clinker includes 64% calcium oxide, 22% silicon dioxide, 6% aluminum oxide, 5% iron oxide and 3% magnesium oxide by mass percentage; the mass content of calcium sulfate dihydrate in the desulfurized gypsum is 99%. The steel slag powder, slag powder, cement clinker and desulfurized gypsum are mixed evenly in mass percentages of 10%:70%:15%:5% to obtain a cementitious material.

[0081] The admixture is an early strength water reducing agent, and the mass content of β-naphthalenesulfonate formaldehyde condensate in the early strength water reducing agent is 99%.

[0082] The above raw coal, prepared cementitious material, admixture and water are mixed evenly according to the above weight portions to obtain coal aggregate that meets the cementitious support material, and then injected into a 100mm×100mm×100mm cubic mold, and then placed on a vibration table for vibration for 5 minutes. The sample is demoulded after 6 hours, and placed in a curing box at a temperature of 20°C and a relative humidity of 95% for curing for 3 to 28 days, and the unconfined compressive strength of the support material test blocks after curing for 3 days and 28 days are tested respectively.

[0083] Embodiment 9:

[0084] A coal aggregate composite cementitious supporting material comprises the following components in parts by weight: 100 parts of raw coal, 40 parts of cementitious material, 0.6 parts of admixture and 20 parts of water.

[0085] The particle size of the raw coal is ≤20 mm, wherein the mass percentages of the raw coal with particle sizes below 5 mm, 5-10 mm and 10-20 mm are 55%:25%:20%.

[0086] The steel slag and ore slag are dried in an oven at 110°C for 5 hours, ground in a φ500mm*500mm mill and then sieved through 200 meshes; the steel slag powder includes 38% calcium oxide, 19% silicon dioxide, 24% iron oxide, 6% aluminum oxide and 13% magnesium oxide by mass percentage; the ore slag powder includes 37% calcium oxide, 34% silicon dioxide, 2% iron oxide, 16% aluminum oxide and 11% magnesium oxide by mass percentage. The cement clinker and desulfurized gypsum are sieved through a 3mm sieve respectively; the cement clinker includes 64% calcium oxide, 22% silicon dioxide, 6% aluminum oxide, 5% iron oxide and 3% magnesium oxide by mass percentage; the mass content of calcium sulfate dihydrate in the desulfurized gypsum is 99%. The steel slag powder, ore slag powder, cement clinker and desulfurized gypsum are mixed evenly in the mass percentages of 10%:75%:5%:10% to obtain a cementitious material.

[0087] The admixture is an early strength water reducing agent, and the mass content of β-naphthalenesulfonate formaldehyde condensate in the early strength water reducing agent is 99%.

[0088] The above raw coal, prepared cementitious material, admixture and water are mixed evenly according to the above weight portions to obtain coal aggregate that meets the cementitious support material, and then injected into a 100mm×100mm×100mm cubic mold, and then placed on a vibration table for vibration for 5 minutes. The sample is demoulded after 6 hours, and placed in a curing box at a temperature of 20°C and a relative humidity of 95% for curing for 3 to 28 days, and the unconfined compressive strength of the support material test blocks after curing for 3 days and 28 days are tested respectively.

[0089] Embodiment 10:

[0090] A coal aggregate composite gelling support material comprises the following components in parts by weight: 120 parts of raw coal, 40 parts of gelling material, 0.6 parts of admixture and 20 parts of water.

[0091] The particle size of the raw coal is ≤20 mm, wherein the mass percentages of the raw coal with particle sizes below 5 mm, 5-10 mm and 10-20 mm are 55%:25%:20%.

[0092] The steel slag and ore slag are dried in an oven at 110°C for 5 hours, ground in a φ500mm*500mm mill and then sieved through 200 meshes; the steel slag powder includes 38% calcium oxide, 19% silicon dioxide, 24% iron oxide, 6% aluminum oxide and 13% magnesium oxide by mass percentage; the ore slag powder includes 37% calcium oxide, 34% silicon dioxide, 2% iron oxide, 16% aluminum oxide and 11% magnesium oxide by mass percentage. The cement clinker and desulfurized gypsum are sieved through a 3mm sieve respectively; the cement clinker includes 64% calcium oxide, 22% silicon dioxide, 6% aluminum oxide, 5% iron oxide and 3% magnesium oxide by mass percentage; the mass content of calcium sulfate dihydrate in the desulfurized gypsum is 99%. The steel slag powder, ore slag powder, cement clinker and desulfurized gypsum are mixed evenly in the mass percentages of 10%:75%:5%:10% to obtain a cementitious material.

[0093] The admixture is an early strength water reducing agent, and the mass content of β-naphthalenesulfonate formaldehyde condensate in the early strength water reducing agent is 99%.

[0094] The above raw coal, prepared cementitious material, admixture and water are mixed evenly according to the above weight portions to obtain coal aggregate that meets the cementitious support material, and then injected into a 100mm×100mm×100mm cubic mold, and then placed on a vibration table for vibration for 5 minutes. The sample is demoulded after 6 hours, and placed in a curing box at a temperature of 20°C and a relative humidity of 95% for curing for 3 to 28 days, and the unconfined compressive strength of the support material test blocks after curing for 3 days and 28 days are tested respectively.

[0095] Embodiment 11:

[0096] A coal aggregate composite cementitious supporting material comprises the following components in parts by weight: 120 parts of raw coal, 60 parts of cementitious material, 0.9 parts of admixture and 30 parts of water.

[0097] The particle size of the raw coal is ≤20 mm, wherein the mass percentages of the raw coal with particle sizes below 5 mm, 5-10 mm and 10-20 mm are 55%:25%:20%.

[0098] The steel slag and ore slag are dried in an oven at 110°C for 5 hours, ground in a φ500mm*500mm mill and then sieved through 200 meshes; the steel slag powder includes 38% calcium oxide, 19% silicon dioxide, 24% iron oxide, 6% aluminum oxide and 13% magnesium oxide by mass percentage; the ore slag powder includes 37% calcium oxide, 34% silicon dioxide, 2% iron oxide, 16% aluminum oxide and 11% magnesium oxide by mass percentage. The cement clinker and desulfurized gypsum are sieved through a 3mm sieve respectively; the cement clinker includes 64% calcium oxide, 22% silicon dioxide, 6% aluminum oxide, 5% iron oxide and 3% magnesium oxide by mass percentage; the mass content of calcium sulfate dihydrate in the desulfurized gypsum is 99%. The steel slag powder, ore slag powder, cement clinker and desulfurized gypsum are mixed evenly in the mass percentages of 10%:75%:5%:10% to obtain a cementitious material.

[0099] The admixture is an early strength water reducing agent, and the mass content of β-naphthalenesulfonate formaldehyde condensate in the early strength water reducing agent is 99%.

[0100] The above raw coal, prepared cementitious material, admixture and water are mixed evenly according to the above weight portions to obtain coal aggregate that meets the cementitious support material, and then injected into a 100mm×100mm×100mm cubic mold, and then placed on a vibration table for vibration for 5 minutes. The sample is demoulded after 6 hours, and placed in a curing box at a temperature of 20°C and a relative humidity of 95% for curing for 3 to 28 days, and the unconfined compressive strength of the support material test blocks after curing for 3 days and 28 days are tested respectively.

[0101] Comparative Example 1: PO42.5 cement was used instead of the cementitious material in Example 2. Other materials, preparation methods and demolding and curing conditions were the same as those in Example 2 to obtain a coal aggregate composite cementitious support material. The unconfined compressive strength of the support material test blocks was tested after curing for 3 days and 28 days respectively.

[0102] Comparative Example 2: PO42.5 cement was used instead of the cementitious material in Example 9. Other materials, preparation methods and demolding and curing conditions were the same as those in Example 9 to obtain a coal aggregate composite cementitious support material. The unconfined compressive strength of the support material test blocks was tested after curing for 3 days and 28 days respectively.

[0103] The demoulding time of the coal aggregate composite cementitious support material test blocks obtained in Examples 1-11 and Comparative Examples 1-2, and the unconfined compressive strength after curing for 3 days and 28 days are shown in Table 1.

[0104] Table 1

[0105]

[0106] It can be seen from Table 1 that the coal aggregate composite cementitious support material prepared by the raw materials disclosed in the present invention is compared with the support material prepared by PO42.5 cement. Under the conditions that the mass parts of raw coal, admixture and water are the same and the cementitious material and PO42.5 cement are equal, the compressive strength of the coal aggregate composite cementitious support material obtained by the present invention is greater than that of the support material prepared by PO42.5 cement, and a large amount of solid wastes such as steel slag, slag, and desulfurized gypsum are effectively utilized, thereby improving the comprehensive utilization value of solid wastes.

[0107] Those skilled in the art to which the present application belongs may make various modifications or additions to the specific embodiments described or replace them in a similar manner, but they will not deviate from the inventive concept of the present application or exceed the scope defined by the attached claims.

Claims

1. A coal aggregate composite cementitious support material, characterized in that: The invention comprises the following raw materials in parts by weight: 100-120 parts of raw coal, 40-60 parts of cementitious material, 0.6-0.9 parts of admixture and 20-30 parts of water.

2. A coal aggregate composite cementitious support material according to claim 1, characterized in that: The particle size of the raw coal is ≤20 mm, wherein the mass percentages of the raw coal with particle sizes below 5 mm, 5-10 mm and 10-20 mm are 45%-55%: 25%-35%: 15%-20%.

3. A coal aggregate composite cementitious support material according to claim 2, characterized in that: The cementitious material consists of steel slag powder, slag powder, cement clinker and desulfurized gypsum powder, and the mass percentages of the steel slag powder, slag powder, cement clinker and desulfurized gypsum powder are 6%-12%: 55%-75%: 5%-20%: 3%-12%.

4. The coal aggregate composite cementitious supporting material according to claim 3, characterized in that: The steel slag powder comprises 35%-40% of calcium oxide, 14%-20% of silicon dioxide, 20%-25% of iron oxide, 1%-7% of aluminum oxide and 8%-14% of magnesium oxide by mass percentage; the slag powder comprises 35%-40% of calcium oxide, 30%-34% of silicon dioxide, 1%-5% of iron oxide, 13%-17% of aluminum oxide and 7%-13% of magnesium oxide by mass percentage; the cement clinker comprises 60%-70% of calcium oxide, 20%-24% of silicon dioxide, 4%-8% of aluminum oxide, 2%-5% of iron oxide and 1%-4% of magnesium oxide by mass percentage; the mass content of calcium sulfate dihydrate in the desulfurized gypsum is 93%-99%; the admixture is an early strength water reducer, and the mass content of β-naphthalenesulfonate formaldehyde condensate in the early strength water reducer is 98%-99%.

5. The coal aggregate composite cementitious support material according to claim 4, characterized in that: The mass percentages of the raw coal particles with diameters of less than 5 mm, 5-10 mm and 10-20 mm are 50%-55%: 25%-30%: 15%-20%.

6. The coal aggregate composite cementitious support material according to claim 5, characterized in that: The dosage of the early strength water reducing agent accounts for 1.2%-1.5% of the mass of the cementitious material.

7. A coal aggregate composite cementitious support material according to any one of claims 1 to 6, characterized in that: The amount of water added accounts for 40%-60% of the mass of the cementitious material.

8. A method for preparing a coal aggregate composite cementitious support material, characterized in that: The following steps are involved: S1, crushing, screening and grading the raw coal for standby use; S2, drying, powdering and sieving the steel slag and slag in an oven respectively, crushing and sieving the cement clinker, crushing and sieving the desulfurized gypsum, weighing the steel slag powder, slag powder, cement clinker and desulfurized gypsum powder according to the mixing ratio and uniformly stirring to obtain a cementitious material; S3, weighing the raw coal obtained in step S1, the cementitious material obtained in step S2, the admixture and water according to the mixing ratio, and uniformly stirring them to obtain the coal aggregate composite cementitious support material; S4. Inject the coal aggregate composite gelling support material obtained in step S3 into the mold, and then place it on a vibration table to vibrate to remove bubbles. After that, demould the sample and place it in a constant temperature and humidity standard curing box for curing.

9. The method for preparing a coal aggregate composite cementitious support material according to claim 8, characterized in that: In the step S1, the raw coal is sieved through 20mm, 10mm and 5mm sieves respectively, and then the particle sizes are classified into less than 5mm, 5-10mm and 10-20mm for standby use; the steel slag and slag in the step S2 are dried in an oven at 105-115°C for 3-6h, ground in a φ500mm*500mm mill and then sieved through 200 mesh for standby use; in the step S2, the cement clinker is sieved through a 3mm sieve for standby use; the desulfurized gypsum in the step S2 is sieved through a 3mm sieve for standby use; in the step S4, the support material is injected into a 100mm×100mm×100mm cubic mold, and then placed on a vibration table for 3-5min, the sample is demoulded after 5-6h, and placed in a curing box with a temperature of 20°C±2°C and a relative humidity of ≥95% for 3 to 28 days of curing, and the unconfined compressive strength of the support material test block after curing for 3 days and 28 days is tested respectively.

10. Use of the coal aggregate composite cementitious support material according to claim 7 or the coal aggregate composite cementitious support material prepared by the preparation method according to claim 9 in supporting empty lanes at working faces in mines.

Citation Information

Patent Citations

  • Preparation method for artificial fish reef concrete material with slag as main raw material

    CN103159448A